Increased Rates of Hospitalized Children with Type 1 and Type 2 Diabetes Mellitus in Central Brooklyn during the COVID-19 Pandemic - Assia Miller; Shalu Joseph; Ahmed Badran; Vatcharapan Umpaichitra; Renee Bargman; Vivian L. Chin (Hindawi Limited, 2023)
Following reports of increased new-onset diabetes and worse severity of DKA for children with diabetes following SARS-CoV-2 infection, we studied hospitalization rates for children with type 1 diabetes (T1DM) and type 2 diabetes (T2DM) in our center during the citywide shutdown. Methods. We conducted a retrospective chart review of children admitted to our two hospitals from January 1, 2018, to December 31, 2020. We included ICD-10 codes for diabetic ketoacidosis (DKA), hyperglycemic hyperosmolar syndrome (HHS), and hyperglycemia only. Results. We included 132 patients with 214 hospitalizations: 157 T1DM, 41 T2DM, and 16 others (14 steroid induced, 2 MODY). Overall admissions rates for patients with all types of diabetes were 3.08% in 2018 to 3.54% in 2019 (p=0.0120) and 4.73% in 2020 (p=0.0772). Although there was no increase of T1DM admissions across all 3 years, T2DM admission rates increased from 0.29% to 1.47% (p=0.0056). Newly diagnosed T1DM rates increased from 0.34% in 2018 to 1.28% (p=0.002) in 2020, and new-onset T2DM rates also increased from 0.14% in 2018 to 0.9% in 2020 (p=0.0012). Rates of new-onset diabetes presenting with DKA increased from 0.24% in 2018 to 0.96% in 2020 (p=0.0014). HHS increased from 0.1% in 2018 to 0.45% in 2020 (p=0.044). The severity of DKA in newly diagnosed was unaffected (p=0.1582). Only 3 patients tested positive for SARS-CoV-2 infection by PCR. Conclusion. Our urban medical center is located in Central Brooklyn and serves a majority who are Black. This is the first study investigating pediatric diabetes cases admitted to Brooklyn during the first wave of the pandemic. Despite the overall pediatric admissions declining in 2020 due to the citywide shutdown, overall hospitalization rates in children with T2DM and in new-onset T1DM and T2DM increased, which is not directly associated with active SARS-CoV-2 infection. More studies are needed to elucidate the reason for this observed increase in hospitalization rates.